Induction of bioactive metabolites in Piper psilorhachis C.DC. (Piperaceae) and antibacterial activity by chitosan - Lozada-García , José Armando; Hernández-Suárez, Reyna; Barrientos-Salcedo, Carolina; de la Cruz-Elizondo, Yadeneyro; Vázquez-Martínez, Juan; Carmona-Hernández, Oscar (Ecosistemas y Recursos Agropecuarios, 2025)
Bacterial resistance to antibiotics has driven the search for new chemical compounds with biological activity derived from plants. An example of these bioactive compounds are piperamides, terpenes, alkaloids, and others found in species of the Piper L genus. Additionally, it has been observed that certain elicitors can modify the production of these bioactive compounds. Therefore, the effect of chitosan on the induction of secondary metabolites and antibacterial activity of extracts from Piper psilorhachis C. DC. was evaluated. Three wild populations of P. psilorhachis were selected, and ten individuals per population were sprayed with a 1 mg/mL chitosan solution. Subsequently, leaves were collected, and ethanolic extracts were made, with the total content of flavonoids, phenols, alkaloids, terpenes, and salicylic acid quantified using spectrophotometry. Additionally, a phytochemical profile was determined by GC-MS. Antibacterial activity was evaluated against Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 29212), and Pseudomonas fluorescens (ATCC 15635) using the plate dilution method, and the Minimum Inhibitory Concentration (MIC) was estimated. Chitosan stimulated the production of flavonoids, phenols, and terpenes in all three populations compared to the control, while alkaloids and salicylic acid only significantly increased in one population. Terpene and amide precursors were tentatively identified by GC-MS. Antibacterial activity was significantly higher in the chitosan-treated extracts, with Escherichia coli being the most sensitive strain.
Keywords: Elicitor; Extracts; MIC; Pahogenic bacteria